Alternative and Supplementary Criminal Law Measures to the Provided Punishment Which Restore the Destroyed / Threatened Environment as a Specific Standard of EU Directive 2024/1203 - Mujoska-Trpevska, Elena; Lažetić, Gordana (Glasnik Advokatske komore Vojvodine, 2026)
Environmental protection has become a global challenge, as human activities increasingly threaten ecosystems, threaten biodiversity and significantly negatively impact public health. While regulatory frameworks and law enforcement mechanisms in the civil sector play an essential role in environmental protection, criminal law provides a powerful instrument for deterring law violations, criminal liability of perpetrators and obligations to restore what has been destroyed. Complementarity between criminal and administrative law is essential for preventing and deterring illegal behaviour that harms the environment, but administrative penalties are insufficient. Environmental protection is one of the fundamental objectives of the European Union, as set out in Article 191 of the Treaty on the Functioning of the EU. In the light of the increasing frequency and complexity of environmental crimes, Directive (EU) 2024/1203 was adopted in response to the insufficient effectiveness of the previous instruments (2008/99/EC and 2009/123/EC). One of the aspects that indicated the need for the adoption of the 2024 Directive was the fact that the sanctions under Directive No. 88 of 2008 were insufficient to achieve compliance with EU law on environmental protection through the availability of effective, proportionate and dissuasive criminal sanctions. The 2024 Directive introduces new standards in the definition of criminal offences, sanctions and measures for the restoration and prevention of environmental damage. Namely, penalties should be made more severe in order to enhance their deterrent effect, and to improve the efficiency of detection, investigation, prosecution and adjudication of environmental crimes. Alternative and supplementary measures have a strong preventive function as they reduce the risk of recidivism, encourage environmental responsibility and raise awareness of the consequences of environmental crime. The scale, prevalence and high level of corruption have led some authors to classify this form of crime as a serious “white-collar crime”. Corruption exists since various forms of bribery and influence peddling are involved in high-ranking public officials, politicians and members of law enforcement agencies, but the existence and impact of corruption in the private sector, which, according to GRECO, is of great concern, should not be overlooked. Criminal law should serve as a means of deterring environmental crimes by imposing strict criminal sanctions and measures on those who engage in illegal activities that endanger the environment, as opposed to fines in administrative or civil proceedings.
Keywords: protection of the environment; environmental criminal law; alternative and supplementary measures; restorative measures; judicial protection; good practices